The Social Matrix of Women's Speech at Corinth: The Context and Meaning of the Command to Silence in 1 Corinthians 14:33b–36 - PAIGE, TERENCE (Bulletin for biblical research, 2002)
A reexamination of Greek and Roman culture highlights women's positive role in religion, as Paul also grants, as well as the nuanced but guarded interactions between the sexes. Paul's injunction to women in 1 Cor 14:34–35 was meant to prevent casual interaction between married women and non-family men in the context of worship, not to prevent sacral speech. This behavior was seen as sexually aggressive, bringing shame on these women and the church in society's eyes.